2016
DOI: 10.12965/jer.1632592.296
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the parameters of the high-heel shoe and transfer time of ground reaction force during level walking

Abstract: This study aimed to analyze an effect on the parameters of high-heel shoe and transfer time of ground reaction force during level walking and subjects participated were composed of adult female subjects (n=13) of 20s with height of high heel (0 cm, 9 cm, respectively). Instrument used for the study was 1 set force plate (AMTI-OR9-7) and sampling rate for data collection of analysis parameters was set-up at 1,000 Hz. The revelation of required coefficient of friction (RCOF) maximum showed significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Consequently, our AB-group wore shoes as well to create similar scenarios. Although some studies utilizing high heels suggest type of shoe affects the torque and COP 63 , 64 our participants were instructed to wear comfortable walking shoes whose sole height and stiffness did not vary much. Thus, our participants all wore similar styled/type shoes which may affect our between participant differences, but we believe that this should not impact our conclusion on the effect of co-contractions on postural sway as these were within participant comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, our AB-group wore shoes as well to create similar scenarios. Although some studies utilizing high heels suggest type of shoe affects the torque and COP 63 , 64 our participants were instructed to wear comfortable walking shoes whose sole height and stiffness did not vary much. Thus, our participants all wore similar styled/type shoes which may affect our between participant differences, but we believe that this should not impact our conclusion on the effect of co-contractions on postural sway as these were within participant comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recent studies showed that in the course of manufacturing, besides the design, material and shape of the shoes, more importance should be given to the proper height of the heels. 41 In terms of biomechanics, high-heel shoes cause great toe valgus, musculoskeletal pain, and first-party injury, while there is no conclusive proof for osteoarthritis and second-party injury. 42 A recent study reported a positive association between shoulder discomfort and high-heel shoes among women (p= 0.03).…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…Also female accentuates more on fashion rather than foot function during gait, that is, on high heel shoe. During level walking by high heel shoe did not control efficiently the GRF due to restricted control capacity of coefficient of frictional force and therefore could suggest an inducement of muscle fatigue, heightening a possibility of sliding and falling due to decrease of frictional force (Blanchette et al, 2011; Hyun et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Center of gravity (COG) was accelerated forwardly by three-dimensional external force during bipedal walking. Then the foot overloaded by body weight primarily absorbs and transfers ground reaction force (GRF) to whole body (Hyun et al, 2016). Thus human can adapt various surface environments with bipedal gait, but backpacking of bag and carrier in condition of increased velocity of COG before foot breaking may cause falling injury with difficulty of counteraction of angular momentum (Ko et al, 2017).…”
Section: Introductionmentioning
confidence: 99%